2020
DOI: 10.35342/econder.849015
|View full text |Cite
|
Sign up to set email alerts
|

The Empirical Analysis of the Relationship Between Energy Imports and Renewable Energy in Turkey

Abstract: Bu makale, en az iki hakem tarafından incelenmiş ve intihal içermediği teyit edilmiştir. / This article has been reviewed by at least two referees and scanned via a plagiarism software.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…Importing a large portion of energy affects growth negatively. İnançlı and Akı (2022); Berk and Cin (2018); Orhan and Nergiz (2014) in their studies found for Turkey that high energy imports increase the foreign trade deficit, which then causes the current account deficit to rise. As a result, Türkiye is dependent on imports to increase its production.…”
Section: Discussionmentioning
confidence: 99%
“…Importing a large portion of energy affects growth negatively. İnançlı and Akı (2022); Berk and Cin (2018); Orhan and Nergiz (2014) in their studies found for Turkey that high energy imports increase the foreign trade deficit, which then causes the current account deficit to rise. As a result, Türkiye is dependent on imports to increase its production.…”
Section: Discussionmentioning
confidence: 99%
“…Gelişmekte olan birçok ülke gibi Türkiye'de sınırlı enerji kaynağına sahip olduğundan enerji ihtiyacını karşılamak adına dışa bağımlı bir ülke haline gelmiştir. Enerji talebini ithal ederek karşılayan ülkelerin önemli bir kısmında enerji tüketimi, enerji ithalatı ve dış ticaret açığı arasında pozitif yönlü ve derin bir korelasyonun varlığı yapılan araştırmalarda ortaya çıkmıştır (Demir, 2013;Uysal vd., 2015;İnançlı & Akı, 2020). Enerji ihtiyacını ithal olarak karşılayan ve yeterli döviz girdisi olmayan ülkelerde en önemli sorunlardan biri dış ticaret açığıdır.…”
Section: Yenilenebilir Enerji-dış Ticaret Açığı İlişkisiunclassified